O exercício físico e o bem estar dos idosos - Barreiras e benefícios percebidos: Um estudo realizado num Centro de Convivência em Juiz de Fora, Brasil - Gabriel Oliveira Ritti (2018)
Considering the growth of the elderly population worldwide and in the light of the trend of studies about the positive aspects of human life, the present research aimed to investigate the subjective well-being, the levels of physical exercise, the pros and cons, as well as the barriers and benefits to this practice.A total of 101 elderly, members of a community center in the city of Juiz de Fora, Minas Gerais, Brazil (76.2% women and 23.8% men, mean age 75-76 years) participated in the study. To collect data, a questionnaire was used with questions related to the practice of physical exercises, the barriers and benefits related to this practice and including the translated and adapted versions of the Satisfaction With Life Scale, of the Positive and Negative Affect Schedule, of Decision Balance Scale for Exercise and the Stages of Exercise Change.The results of the research indicated a greater presence of women in community centers and a majority of physical exercise practitioners, both in the research institution and outside. The subjective well-being did not present significant differences between the analyzed variables, however, it was observed the tendency of physically active women reach higher values in this evaluation. The most reported benefit of physical exercise was pain reduction and the most mentioned barrier was lack of motivation. With regard to the evaluation of the decisional balance, physically active individuals presented higher averages in the pros. It is thus confirmed that physical exercises exert great importance for the promotion of the health of the elderly and should be encouraged at all ages to help with aging with increasing quality and less limitations. In this aspect, it is considered the importance of the community center for the elderly to incorporate physical exercises in their activities, as well as the divulgation of the benefits that these practices promote.